A biocubesat compatible payload for future space systems: development of a second generation bammsat payload for stratospheric balloon flight - Shamsul anuar, Aqeel (Cranfield University, 2022)
National space agencies have announced planned long-duration crewed missions beyond Low Earth Orbit. It is critical to understand the impact of long- duration microgravity and especially deep-space radiation exposure on humans. There is a knowledge gap concerning the effects of the space environment on humans, our human microbiome and associated Earth biology needed to support human activities in space. There is also a renaissance in the space industry, as seen in increased space activities and commercialisation. This is driven by the growing international activities, shifting funding landscape, and change in commercialisation activities. It is thought that the space industry is at an inflexion point for a full-scale microgravity research programme (DiFrancesco & Olson, 2015). With a newfound interest in life science and microgravity, there is a need for validating data on space-based biological models for terrestrial and space applications. These biological studies require frequent access and many discrete samples before they can be understood and accepted by the scientific community. CubeSats offer opportunities to improve spaceflight access with reduced development time using standardised components, more frequent flight opportunities, and reduced mission costs. Over the last decade, a series of seven bioCubeSats have been launched into orbit by NASA and SpacePharma: GeneSat, PharmaSat, O/OREOS, SporeSat, Dido-2, EcAMSat and Dido-3. The term bioCubeSat refers to a CubeSat with a biological payload onboard. These bioCubeSats proved the feasibility and de-risk the concept of performing a biological experiment on CubeSat. However, these bioCubeSats have design limitation that inhibits the types of organisms and experiments that could be performed onboard. The design limitation affects the number of independent discrete samples, pre-flight handling capability, and sensor types within its system. Cranfield University has been developing an alternative bioCubeSat concept named BAMMsat, for application in LEO and beyond LEO. BAMMsat stands for Bioscience, Astrobiology, Medical, and Material science on CubeSats. The versatile platform builds upon the typical experiment need of these scientific fields, such as i) the need to house multiple samples, ii) the need to maintain viable samples in an appropriate space environment, iii) the need to artificially perturb the samples and (iv) the need to monitor the samples. BAMMsat was developed to address the knowledge gap to fly a broader range of organisms and experiments enabled by its Rotary Valve, Multi-Chamber Sample Disc, and richer sensor offering. BAMMsat could be an asset to provide autonomous and high-throughput experiments as an R&D instrument for space bioscience and biotechnology. At a lower entry cost combined with the capability to perform an autonomous in-situ data measurement, BAMMsat could increase life science in microgravity either for using space for a terrestrial application and supporting future human exploration of the Moon and Mars. The PhD thesis reports on PhD research performed to advance the BAMMsat concept developing the 1st gen. laboratory breadboard (TRL 4) into a 2nd gen. technology demonstration hardware (TRL 5/6) and bridging the gap towards a 3rd gen. spaceflight mission, currently planned to be on-board the ISS. During the PhD, five different subsystems were developed: the multi-chamber sample disc, rotary valve, compact brightfield microscope, fluidic subsystem, Geneva gear mechanism, and mechanical housing. These subsystems were packaged into a 2U CubeSat payload version of BAMMsat. The 2U CubeSat payload was flown under the BAMMsat-on-BEXUS (BoB) mission. BoB mission was an experiment using live C. elegans from Cranfield University and the University of Exeter, performing a technology and operation demonstration of a 2nd gen. design of BAMMsat hosted on a stratospheric balloon at an altitude of ~28 km above the ground under the BEXUS programme.
Hobbs, Stephen E. - Associate Supervisor
Keywords: CubeSat; C. elegans; bioscience; astrobiology; material; medicine; nanosatellite; BEXUS; stratosphere; technology demonstration